4. Gamma knife surgery for hypothalamic hamartomas causing refractory epilepsy: Long-term outcomes – A prospective observational study. Issue 9 (September 2016) - Martel, Véronique; Mathieu, David; Pinard, Catherine-Andrée; Bourgeois, Pascale; Duval, Julie; Deacon, Charles
Abstract : Object: This prospective observational study, conducted at the CHUS between 2005 and 2016, aims to examine the outcomes of patients who underwent radiosurgery for hypothalamic hamartomas (HHs). Method: Patients were included in the study if they were diagnosed with an HH and refractory epilepsy, without any other suspected seizure focus. After radiosurgery, seizure status was assessed periodically using the Engel Classification. Neuropsychological and quality of life evaluations were performed at baseline and thereafter. A follow-up evaluation was completed ten years after the first Gamma-knife treatment. Results: Thirteen patients, refractory to medical treatment, were included in the study, ranging in age from 12–57 years. Using the Régis Classification, ten patients had smaller hamartomas (Grade I-III) and underwent treatment of the entire lesion. Radiosurgical disconnection was attempted in three patients with larger lesions (Grade IV-VI). One patient was lost to follow-up, and one died from seizure complications following an open surgery for HH. Disconnection was ineffective. Gamma-knife treatment was repeated in three patients in which the first intervention had failed to reduce the seizure burden. Seven patients (58%) had a good outcome (Engel I-II), including five patients who were seizure-free after a mean time of 6.4 months. Five patients (42%) had Engel classification of III or IV. Treatment adverse events included psychotic depression (1) and radiation necrosis (1). Conclusion: Radiosurgery seems to offer a better control of epilepsy secondary to HHs, principally in cases where the entire lesion can be targeted. The authors consider that radiosurgery should be attempted as a first-line surgical therapy for these patients.